Effectiveness of enhanced external counterpulsation in patients with left main disease and angina - Lawson, William E. (Clin Cardiol, 2006)
Background: Enhanced external counterpulsation (EECP) is a noninvasive device that uses three pairs of sequentially inflated pneumatic cuffs applied to the lower extremities and synchronized with the heart beat to provide diastolic augmentation, increase coronary blood pressure and flow, venous return and cardiac output, and decrease afterload. Hypothesis: This study examines the safety and effectiveness of EECP therapy in patients with significant left main coronary artery disease (LMD). Methods: In all, 2,861 patients enrolled in the International EECP Patient Registry (IEPR) were divided into three groups, those without LMD (n = 2,377), those with LMD and prior CABG (n = 431), and those with unbypassed LMD (n = 53). Results: Patients with LMD, with or without prior CABG, were significantly more likely to have triple‐vessel disease (98.1 and 88.7%, respectively) than patients without LMD (41.9%). Post‐EECP, 74% without LMD, 75% with LMD with prior CABG, and 65% with unbypassed LMD improved their Canadian Cardiovascular Society (CCS) angina by at least one class (p = NS). There were no differences in the mean decrease in weekly angina episodes (7.1 vs. 8.0 vs. 7.6) and in the mean frequency of weekly nitroglycerinuse (6.6 vs. 8.1 vs. 8.9). At 6‐month follow‐up, the CCS class improved further in all three groups, and there was a further reduction in mean weekly angina episodes (4.7 vs. 4.6 vs. 5.3) and nitroglycerinuse (6.5 vs. 6.8 vs. 8.2). Kaplan‐Meier life table analysis 8 months after starting EECP demonstrated a major cardiovascular event rate of 11.2% in patients without LMD, 15.6% in LMD with CABG, and 24.3% in LMD without prior CABG. Late mortality in unbypassed LMD was 13.2% (confidence interval [CI] 3.3‐23.1) versus 4.8% (CI 2.7‐7.1) in LMD with CABG, and 2.8% (CI 2.1‐3.5) without LMD (p = 0.0039 by log‐rank test). Conclusion: Enhanced external counterpulsation is equally effective in relieving angina in patients with or without LMD. However, the significantly increased late mortality in patients with LMD without prior CABG suggests that early revascularization should be considered in these patients.